Effect of Cypermethrin on Blood Hematology and Biochemical Parameters in Fresh Water Fish Ctenopharyngodon idella (Grass Carp): Biochemical effect of cypermethrin in fresh water fish - Ullah, Mujeeb; Yousafzai, Ali Muhammad; Muhammad, Ijaz; Ullah, Sobia Atta; Zahid, Muhammad; Khan, Muhammad Ismail; Khan, Khalid; Khayyam, Khayyam; Nayab, Gul E; Aschner , Michael; Alsharif , Khalaf F; Alzahrani, Khalid J; et al. (Cellular and Molecular Biology, 2022)
The insecticide, cypermethrin, adversely affects biochemical parameters in blood and behavior in grass carp (Ctenopharyngodon idella). Fish were obtained from hatchery, reared in the laboratory. Different concentration of cypermethrin were applied. Blood was collected and hematological and biochemical parameters were measured. Biochemical parameters such as, protein levels, cholesterol, phosphorous and calcium in both acute and chronically cypermethrin treated groups decreased, with increasing exposure time from 24h to 15 days with more pronounced effects in the acute groups. Increased glucose, urea, serum glutamic pyruvic transaminase (SGPT), creatinine, and lactate dehydrogenase (LDH) levels were found in both acute and chronic groups with the increasing exposure time. Hematological parameters, such as red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MHCH), and red cell distribution width (RDW) were significantly reduced in both groups as the exposure time increases. However, the numbers of white blood cells (WBC) and platelets were increased. This study established both the acute and chronic toxicity of cypermethrin in grass carp, which likely occurs secondary to altered biochemical and blood parameters.